Legal Aspects of Sharia Insurance Agreements: A Review of Sharia Principles in Insurance Products - Dea salsabila; Salsabila Lubis; Arya Advany; Siti Nurlina; Fatimah Nainggolan (Jurnal Cendikia ISNU SU, 2025)
Sharia insurance is a form of protection agreement based on the principles of Islamic law, as an alternative to the conventional insurance system that contains elements of gharar, maysir, and riba. This research aims to examine the legal aspects of sharia insurance agreements in Indonesia, with an emphasis on the compatibility between the contract in the policy and sharia principles such as ta'awun, tabarru' contract, tijarah contract, as well as the value of justice and transparency. The method used is a literature study with a normative juridical approach, through an examination of laws and regulations, DSN-MUI fatwas, and the results of previous research. The results of the study show that although sharia insurance already has a strong legal basis in positive law and muamalah fiqh, the practice still faces challenges in terms of the clarity of the contract, the management of participant funds, and the dispute resolution mechanism. Therefore, harmonization between national law and Islamic law, as well as strengthening technical regulations and education to the public, is needed to realize a sharia insurance system that is fully sharia-compliant.